A pilot study of a neuroscience-based, harm minimisation programme in schools and youth centres in Australia. Issue 2 (6th February 2020) - Debenham, Jennifer; Birrell, Louise; Champion, Katrina; Askovic, Mina; Newton, Nicola
Abstract : Objectives: The primary aim is to evaluate the feasibility of a newly developed, neuroscience-based, alcohol and other drug (AOD) use prevention programme, ' The Illicit Project ', in Australian older adolescents. The secondary aim is to investigate the impact of the programme on students' drug literacy levels (a combination of knowledge, attitudes and skills). Design: A pilot study examining the feasibility of The Illicit Project in Australian schools was conducted. Participants: Students aged 15–19 years from two secondary schools and a youth centre and 11 teachers and health professionals from various organisations in Sydney were recruited. Intervention: The intervention consisted of three 90 min workshops delivered by trained facilitators within a month. Primary and secondary measures: Students completed a drug literacy questionnaire before and after intervention. All participants (students, teachers and health professionals) completed an evaluation questionnaire postprogramme delivery. A paired-sample t-test and descriptive analytics were performed. Results: Students (n=169) demonstrated a significant increase in drug literacy levels from preintervention to postintervention (t(169) = −13.22, p<0.0001). Of students evaluating the programme (n=252), over threequarters agreed that T he Illicit Project was good or very good (76%), that the neuroscience content was interesting (76%) and relevant (81%), and that they plan to apply the concepts learnt to their own lives (80%). In addition, all teachers and health professionals (n=11) agreed that the programme was feasible and valid for schools and perceived the programme to be effective in reducing the harms and use of AOD. Conclusions: There is evidence to suggest that The Illicit Project is credible and feasible in the school environment and there are preliminary data to suggest it may help to improve drug literacy levels in young people. A large-scale evaluation trial of the intervention will be conducted to determine the programme's effectiveness in minimising the harms of AOD in older adolescents.